Analisa Penanaman Dana dalam Aset Produktif dan Implikasinya Terhadap Permodalan: (Studi Kasus pada Bank BJB Syariah) (AL AMWAL (HUKUM EKONOMI SYARIAH), 2019)
Survival of a bank depends on how the bank can manage their earning assets and the readiness of the bank in the face of risks arising from assets that are embedded. The good quality of assets invested can generate the optimal profit, where the income will be a factor enhancer bank capital. The purpose of this study is to find out how the management of assets which are carried out planting bank bjb syariah and the extent of its influence on their capital so that research can be useful for both theoretical and practical science. Based on statistical analysis using SPSS version 12.0, which indicates that the results obtained through correlation tests, all variables have a perfect relationship is positive ( + ), in which the Receivables Financing and has a very strong relationship with Capital, SWBIs have a strong relationship, whereas placement has a moderate relationship . Financing investment of funds in the form of a very strong influence on the Capital than any other form. Therefore bjb sharia banks should pay particular attention to the distribution of funds in the form of both quality and quantity Financing.